Efficient Enrichment of Hepatic Cancer Stem-Like Cells from a Primary Rat HCC Model via a Density Gradient Centrifugation-Centered Method - Liu, Wei-hui; Wang, Xing; You, Nan; Tao, Kai-shan; Wang, Tao; Tang, Li-jun; Dou, Ke-feng (PLOS ONE, 2012)
Background Because few definitive markers are available for hepatic cancer stem cells (HCSCs), based on physical rather than immunochemical properties, we applied a novel method to enrich HCSCs. Methodology After hepatic tumor cells (HTCs) were first isolated from diethylinitrosamine-induced F344 rat HCC model using percoll discontinuous gradient centrifugation (PDGC) and purified via differential trypsinization and differential attachment (DTDA), they were separated into four fractions using percoll continuous gradient centrifugation (PCGC) and sequentially designated as fractions I–IV (FI–IV). Morphological characteristics, mRNA and protein levels of stem cell markers, proliferative abilities, induced differentiation, in vitro migratory capacities, in vitro chemo-resistant capacities, and in vivo malignant capacities were determined for the cells of each fraction. Findings As the density of cells increased, 22.18%, 11.62%, 4.73% and 61.47% of primary cultured HTCs were segregated in FI–FIV, respectively. The cells from FIII (density between 1.041 and 1.062 g/ml) displayed a higher nuclear-cytoplasmic ratio and fewer organelles and expressed higher levels of stem cell markers (AFP, EpCAM and CD133) than cells from other fractions (P<0.01). Additionally, in vitro, the cells from FIII showed a greater capacity to self-renew, differentiate into mature HTCs, transit across membranes, close scratches, and carry resistance to chemotherapy than did cells from any other fraction; in vivo, injection of only 1×104 cells from FIII could generate tumors not only in subcutaneous tissue but also in the livers of nude mice. Conclusions Through our novel method, HCSC-like cells were successfully enriched in FIII. This study will greatly contribute to two important areas of biological interest: CSC isolation and HCC therapy.